Epistemic Foundations of Solution Concepts in Game Theory: An Introduction - Giacomo Bonanno; Klaus Nehring (University of California, Department of Economics, 1997)
We give an introduction to the literature on the epistemic foundations of solution concepts in game theory. Only normal-form games are considered. The solution concepts analyzed are rationalizability, strong rationalizability, correlated equilibrium and Nash equilibrium. The analysis is carried out locally in terms of properties of the belief hierarchies. Several examples are used throughout to illustrate definitions and concepts.
Keywords: 330